Development and Validation of a Bioanalytical Method to Determine Empagliflozin in Human Plasma Using UPLC-MS/MS - Sumithra, Mani; Andrew, David John; Aanandhi, Muthukumar Vijey (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: The study we are conducting aims to establish a validated method for measuring empagliflozin in plasma using UPLC MS/MS. Materials and Methods: Sodium-Glucose co Transporter inhibitors (SGLTi), a novel class of diabetes medication. Non-insulin dependent diabetes and adult-onset diabetes were the prior names for type 2 diabetes. Empagliflozin was the first SGLT2-inhibitor a drug used that reduced the risk of cardiovascular risk those with type 2 diabetes and pre-existing cardiovascular disease. The empagliflozin D4 as Internal Solution (IS). Liquid-liquid extraction was used to achieve separation on Synergi 2.5μ Fusion-Reverse phase 100A (100 mm×2.0 mm), 2.5 μm column. Mixture of Methanol: As a mobile phase, 0.2% formic acid in a 75:25 volumetric ratio is utilised. The flow rate is set at 0.3μl/min. The calibration curve is linear and plotted. Results: The developed method is accurate, precise, sensitive method for determination of empagliflozin from human plasma solution. Ethyl acetate and water in HPLC grade are preferred solvent for empagliflozin. Performing LLE extraction with centrifuge and LV Nitrogen Evaporator it with Ethyl acetate and water. Ethyl acetate is used as non-polar solvent and water is used as polar solvent for liquid-liquid extraction. LLE is a low cost extraction process compare to solid liquid extraction. The reported method is suitable for bioequivalence and pharmacokinetic studies.
Keywords: Type 2 diabetes (T2D); Empagliflozin; Human Plasma; UPLC-MS/MS; Type 2 diabetes (T2D); Empagliflozin; Human Plasma; UPLC-MS/MS